BDI Funds Allocation Through Kotaku Towards The Development of Pasar Lama Kelurahan Banjarmasin Tengah Viewed from The Impact and Islamic Economy - S. Purnamasari (Dwijendra University, 2020)
Islam sees economic development as the growth of human maturity, where the material progress that is currently inevitable and that must be supported by the strength of spiritual maturity so that prosperity is achieved. Benefit can be achieved when what emerges from a process is benefit and blessing. However, not everything that is beneficial can provide a blessing. The impact of the allocation of BDI KOTAKU funds on the economic development of Pasar Lama Kelurahan, Banjarmasin Tengah in 2017 was well utilized by the allocation of its use and could improve the economy and welfare of the citizens. However, when viewed from the perspective of Islamic economics, this is not enough even optimal in terms of funding because it is still not optimal use of existing and owned resources, it still depends on external sources / foreign debt which incidentally is interest-based so that there is an impact on funding dependency and make the nation's next generation dependent to the West, bearing the burden of debt and interest on its loans. This is what is called in the Islamic Economy with a useful concept but not a blessing / does not give blessing because of the interest / ribawi system. Thus the economic approach to the development of Sharia is needed to focus on development instruments that are compatible with religion / sharia and culture / local wisdom (local wisdom) so that existing resources can be utilized properly and benefits can be realized.